Advances in computers. volume 59 - Zelkowitz, Marvin V., 1945- ([S.l.] : Academic Press, 2003)
Since 1960, Advances in Computers has chronicled the constantly shifting theories and methods of Information Technology which greatly shapes our lives today This volume, the 59th in the series, presents two general themes. The first 4 papers discuss tool use in developing software - how groups work together to produce a product, and why the very industries that need them often do NOT adopt such tools. The fifth paper addresses a current hardware issue - cache coherence. As we build faster machines, a way to increase performance is to have multiple CPUs working on solving the same problem. This requires two or more CPUs to address the same memory at the same time. The cache coherence problem is how to allow both machines to access the same memory without "stepping on each others toes" so that memory gets lost or corrupted *In depth surveys and tutorials on new computer technology *Well-known authors and researchers in the field *Broad overview of many important developments *Extensive bibliographies with most chapters *Four out of 5 chapters focus on software developemnt technology and should appeal to a software development organization or a university course on software development practices.
Preface. -- Contributors. -- Collaborative Development Environments, G. Booch and A.W. Brown. -- Tool Support for Experience-based Software Development Methodologies, S. Henninger. -- Why New Software Processes Are Not Adopted, S. Rifkin. -- Impact Analysis in Software Evolution, M. Lindvall. -- Coherence protocols for Bus-based and Scalable Multiprocesors, Internet, and Wireless Distributed Computing Environments: A Survey, J. Sustersic and A. Hurson.
Keywords: Electronic data processing; Computers; Electronic books